'Putting a Foot in the Door': Volunteer Hiring and Organizational Form. (28th October 2015) - Vlassopoulos, Michael
Abstract : Volunteering often acts as a stepping stone into a paid position. This paper provides an explanation for the fact that non‐profit employers are uniquely able to attract volunteers with social concerns and career aspirations and for the related observation that non‐profits figure prominently in mission‐related activities. The theory is predicated on that—by committing to not distributing profits—non‐profit incorporation relaxes the incentive constraint that employers face when implicitly contracting with volunteers. The not‐for‐profit commitment is shown to be effective only in activities where producers, who can choose to be for‐profit or non‐profit, care about the level of the service being provided.